2019
DOI: 10.3390/su11184922
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Economic Effects on the Greening and Recovery of the Sludge Waste Resulting from the Biogas Production Activity

Abstract: Starting from identifying an upward trend in waste disposal costs at the municipal landfill, the research aims to analyze the viability of investment to integrate a compost platform, which transforms the sludge resulting from the biogas production process into a soil improver for agricultural land. The economic entity analyzed activates agri-food and uses a biogas plant as a management tool for the waste from slaughtering chickens, to obtain biogas, heat, and electricity. The study is carried out through the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Awe et al, (2017) demonstrated that is an effective renewable energy sources for fuel and chemicals production, including hydrogen and synthetic gas. Additionally, Ionescu et al (2019) reported significant revenue growth (37.96%) and profit (53.175) in Romania from the application of biogas, underscoring its environmental and economic benefits. Further research has explored societal, cultural, and economic aspects of biogas adoption, particularly among farmers (Dobers, 2019;Emmann et al, 2013;Francois, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Awe et al, (2017) demonstrated that is an effective renewable energy sources for fuel and chemicals production, including hydrogen and synthetic gas. Additionally, Ionescu et al (2019) reported significant revenue growth (37.96%) and profit (53.175) in Romania from the application of biogas, underscoring its environmental and economic benefits. Further research has explored societal, cultural, and economic aspects of biogas adoption, particularly among farmers (Dobers, 2019;Emmann et al, 2013;Francois, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emergency Ordinance 48/2017 for the amendment and supplementation of Government Emergency Ordinance 196/2005 on the Environment Fund [42] suspended the landfill waste disposal charge until January 2019. In this way, the waste to landfill disposal was no longer fined [43]. Starting from 1 January 2019, the charge for landfill waste disposal has been reintroduced, in a sum of 16.9 Eur/t in 2019 and 25.1 Eur/t in 2020.…”
Section: Measurements Of the Economic Effects Of Biosolids For Water Utilitiesmentioning
confidence: 99%